PERAN SPRITUALITAS ISLAM DALAM TERAPI KESEHATAN MENTAL: ANALISIS PERSPEKTIF AL-QUR’AN - Salman; Muhmmad Darul Amin Sitorus; Syawaluddin Nasution (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
The purpose of this research is to examine the integration of Islamic spirituality in mental health psychotherapy: an analysis from the Qur’anic perspective. This study is a type of library research. The data for this study was collected, examined, and then described using the gathered information. The data collection methods were sourced from relevant books, texts, and articles. This research also employed descriptive analysis techniques aimed at clarifying positive perceptions towards spiritual training activities based on the Qur’anic perspective. The findings indicate that the integration of Islamic spirituality can have implications for mental health. Spiritual training activities include two main components: therapy through reading and understanding the meanings of the Qur’an as shifa (healing) and daily repentance prayers (dua taubah) performed by patients/clients during the rehabilitation process